2014
DOI: 10.1136/bmjresp-2014-000035
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the challenges and facilitators of implementing a COPD care bundle

Abstract: BackgroundCare bundles have been shown to improve outcomes, reduce hospital readmissions and reduce length of hospital stay; therefore increasing the speed of uptake and delivery of care bundles should be a priority in order to deliver more timely improvements and consistent high-quality care. Previous studies have detailed the difficulties of obtaining full compliance to bundle elements but few have described the underlying reasons for this. In order to improve future implementation this paper investigates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 24 publications
2
45
1
Order By: Relevance
“…While community and primary health care providers saw education and training as a more vital contributor to uptake, they did not describe lack of time as a barrier. Contrary to our findings, Lennox et al [36] found lack of time ("staff too busy") as the most prominent barrier to bundle implementation in their study on implementation of a COPD care bundle in hospitals in London (UK). However, similar to our study results, they recognized staff shortages, staff engagement, and added workload among the top four barriers to bundle implementation, barriers that the most robust implementation plan would be challenged with.…”
Section: Discussioncontrasting
confidence: 99%
“…While community and primary health care providers saw education and training as a more vital contributor to uptake, they did not describe lack of time as a barrier. Contrary to our findings, Lennox et al [36] found lack of time ("staff too busy") as the most prominent barrier to bundle implementation in their study on implementation of a COPD care bundle in hospitals in London (UK). However, similar to our study results, they recognized staff shortages, staff engagement, and added workload among the top four barriers to bundle implementation, barriers that the most robust implementation plan would be challenged with.…”
Section: Discussioncontrasting
confidence: 99%
“…NIHR Journals Library www.journalslibrary.nihr.ac.uk to implementation in a systematic way. Lennox et al, 42 working as part of the National Institute for Health Research (NIHR) Collaboration for Leadership in Applied Health Research and Care for Northwest London, interviewed staff members involved in a multihospital QI project implementing COPD care bundles. They identified 28 challenges that impacted negatively on bundle implementation across five themes, including staffing, infrastructure, process, use of improvement methodology and patient and public involvement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…on whether or not to implement guidelines. This barrier has been pointed out in several studies carried out in various settings [9][10][11][12][13][14][15][16][17][18][19][20][21][22] . Moreover, Chapman et al has observed that if a team practice is tailored according to the team head, the choice of which CPG to adopt might change if a new team head is appointed [19] .…”
Section: Table 1: Demographics Of Participantsmentioning
confidence: 99%
“…It can be argued that the physicians in this study perceived their lack of awareness of the guideline and a lack of knowledge as a barrier to implementation. This has been one of the most reported barriers across studies in this topic [20][21][22]24] . This lack of knowledge could be divided into two types; first, the lack of knowledge about the guideline itself which has been labeled as awareness in some studies [23,25] , and second, lack of knowledge in the usage or application of the guidelines, which has been labeled as skills in other studies [22,24] .…”
Section: Table 1: Demographics Of Participantsmentioning
confidence: 99%